Demetaphorization, Anatomy, and the Semiotics of the Reformation in Early Modern Revenge Tragedy - Kiss, Attila (Studia Anglica Posnaniensia, 2018)
Reformation theology induced a profound thanatological crisis in the semiotics of the human being and the body. The Protestant Reformation discontinued numerous practices of intercession and communal ritual, and the early modern subject was left vulnerable in the face of death. The English Renaissance stage played out these anxieties within the larger context of the epistemological uncertainties of the age, employing violence and the anatomization of the body as representational techniques. While theories of language and tragic poetry oscillated between different ideas of imitatio (granting priority to the model) and mimesis (with preference for the creative and individual nature of the copy), the new anatomical interest and dissective perspectives also had their effects on the rhetorical practices of revenge tragedies. In the most shocking moments of these plays, rhetorical tropes suddenly turn into grisly reality, and figures of speech become demetaphorized, literalized. In a double anatomy of body and mind, English Renaissance revenge tragedy simultaneously employs and questions the emblematic and poetic traditions of representation, and the ensuing indeterminacy and ambiguity open paths for a new mimesis.